Modern south asia : history, culture, political economy - Sugata Bose; Ayesha Jalal (New York : Routledge, 2018)
The fifth edition of Modern South Asia draws on the newest historical research and scholarship in the field to interpret and debate key developments in modern South Asian history and historical writing, covering the diverse spectrum of the subcontinent's social, economic and political past. Jointly authored by two leading Indian and Pakistani historians, this definitive study offers a rare depth of historical understanding of the politics, cultures and economies that have shaped the lives of more than a fifth of humanity.
Includes index.
Keywords: History; South Asia - Politics and government - History; South Asia - Economic conditions - History